Bioremediation of Jeram sanitary landfill leachate using selected potential bacteria / Rabi’atul Adawiyah Abd Rahman - Rabi’atul Adawiyah , Abd Rahman (2016)
Over the past decade, generation of municipal solid wastes (MSW) in Malaysia has increased more than 91%. However, MSW management in Malaysia can be considered relatively poor and disorganized. The most preferred of MSW disposal method in Malaysia is through landfilling. The major environmental concern associated with landfill problem is the contamination of leachate into the environment. Due to that problem, this research aimed to characterize leachate and used some selected potential microbes to perform bioremediation on leachate. Utilization of microorganisms such as bacteria in the bioremediation of leachate will help reduce the cost and posed least effect to the environment. Jeram sanitary landfill was used as the source of raw leachate in this study. Leachate was analysed to establish the current characteristics and confirm with previous studies on JSL leachate. The leachate showed deep black colour with a slightly ammoniac odour at pH of 8.38, salinity of 19.30 ppt, conductivity of 35,830 μS/cm and Total Dissolved Solid (TDS) of 20,320 mg/L. BOD5 and COD values were at 1,050 and 11,031.70 mg/L respectively with ratio of 0.09. Ammoniacal nitrogen content recorded at 6,400 mg/L with oil and grease at 4.4 mg/L. Bacteria used in the study namely Bacillus salmalaya, Lysinibacillus sphaericus, Bacillus thuringiensis and Rhodococcus wratislaviensis were previously isolated from the agricultural soil and from a leachate contaminated site in Malaysia. Each strain was grown as a pure culture in NA plates at 33°C for 2 days. The pure strains were used to build up inoculum for leachate remediation. 100 ml of bacteria suspension was added to 900 ml of leachate in each treatment (10% v/v). Leachate were analysed before and after 48 hours of remediation. Results shows that treatment with inoculum which consist of every bacterium used in the study presented a remarkable reducing capacity of oil and grease of 98% and ammoniacal nitrogen at 57% from initial value. On the other hand, the combination of the bacteria also found to be high potential in removing heavy metal in the leachate Pb (86%), Mn (82%), Ba (74%), Al (74%), Zn (73%), As (68%), Ni (66%), Cr (66%) and Fe (63%). In conclusion, the microbial mixtures have showed a good potential in remediating highly heterogeneous and polluted leachate.